Whole-Exome Sequencing Uncovers Novel Causative Variants and Additional Findings in Three Patients Affected by Glycogen Storage Disease Type VI and Fanconi−Bickel Syndrome - Eghbali, Maryam; Fatemi, Kiyana Sadat; Salehpour, Shadab; Abiri, Maryam; Saei, Hassan; Talebi, Saeed; Olyaei, Nasrin Alipour; Yassaee, Vahid Reza; Modarressi, Mohammad Hossein (Frontiers in Genetics, 2021)
Glycogen storage diseases (GSDs) are the heterogeneous group of disorders caused by mutations in at least 30 different genes. Different types of GSDs, especially liver GSDs, take overlapping symptoms and can be clinically indistinguishable. This survey evaluated the use of whole-exome sequencing (WES) for the genetic analysis of the liver GSD-suspected patients in three unrelated families. An in-house filtering pipeline was used to assess rare pathogenic variants in GSD-associated genes, autosomal recessive/mendelian disorder genes (carrier status for genetic counseling subjects), and the ACMG’s list of 59 actionable genes. For the interpretation of the causative variants and the incidental/secondary findings, ACMG guidelines were applied. Additionally, we have explored PharmGKB class IA/IB pharmacogenetic variants. The segregation analysis was performed using Sanger sequencing for the novel causative variants. Bioinformatics analysis of the exome data in three individuals revealed three novel homozygous causative variants in the GSD-associated genes. The first variant, c.298_307delATGATCAACC in PYGL gene has related to HERS disease (GSD VI). Both variants of c.1043dupT and c.613-1G > C in SLC2A2 gene have been associated with Fanconi-Bickel syndrome (GSDXI). Eight pathogenic/likely pathogenic medical actionable findings in Mendelian disease genes and 10 pharmacogenetic variants with underlying drug response phenotypes have been identified. No known/expected pathogenic variants were detected in the ACMG’s list of 59 actionable genes. The logical filtering steps can help in finding other medical actionable secondary/incidental findings as well as effectively identifying the causative variants in heterogeneous conditions such as GSDs. Three novel variants related to GSD genes recognized in liver GSD-suspected patients with early infantile and childhood-age onset.